(untitled) (Jurnal Destinasi Pariwisata, 2025)
This thesis investigates the branding strategies employed by Tupai Emas Agrotourism in promoting itself as a family-friendly educational tourism destination in Denpasar, Bali. The research has two main objectives: to analyze the actual implementation of educational tourism at the site, and to evaluate the branding efforts used to shape its identity and attract visitors. The study follows a descriptive qualitative approach, with data collected through in depth interviews involving key stakeholders such as managers, family visitors, and educators, in addition to field observations and document analysis. The findings demonstrate that Tupai Emas Agrotourism adopts an interactive, nature-based educational concept that provides learning experiences especially suited for children. Despite this, several limitations were identified, including the lack of structured documentation, limited staff training, and insufficient educational facilities. From a branding standpoint, efforts have been made through digital media and curated experiences to leave a lasting impression on visitors. However, further improvement is needed in strengthening brand awareness, perceived quality, brand associations, and visitor loyalty. The application of Segmentation, Targeting, and Positioning (STP) strategies is considered appropriate, focusing primarily on families and educational groups. This study is expected to offer both academic contributions to the discourse on tourism branding and practical insights for agrotourism operators aiming to refine their promotional strategies and enhance visitor engagement.